Gastritis Stages in Monozygotic and Dizygotic Dyspeptic Twins - Urba, Mindaugas (Gastroenterol Res Pract, 2020)
BACKGROUND: The progression of Helicobacter pylori-associated gastritis towards atrophic gastritis is modulated by host-related and environmental factors. Studies that explore the possible involvement of host-related versus environmental factors in the development of gastritis phenotype induced by H. pylori are highly needed. AIMS: Our study was aimed at investigating the phenotype of H. pylori-associated gastritis in two cohorts of monozygotic and dizygotic twins, using the OLGA/OLGIM gastritis staging system. METHODS: Two cohorts of monozygotic (14 pairs) and dizygotic (15 pairs) dyspeptic twins prospectively underwent endoscopy with biopsy sampling based on Sydney protocol. H. pylori status and OLGA/OLGIM stages were assessed and compared. RESULTS: The mean age of monozygotic and dizygotic twins was 40.4 and 38.6 years, respectively (p = 0.623). The overall prevalence of H. pylori infection was 51.7%. Among the 14 monozygotic twin pairs, five pairs were H. pylori-positive, four were H. pylori-negative, and five were H. pylori-discordant. Among the 15 dizygotic twin pairs, five pairs were H. pylori-positive, five were H. pylori-negative, and five were H. pylori-discordant. Concordance for antrum atrophy in monozygotic twins was 78.6% (11/14 pairs) and in dizygotic twins 73.3% (11/15 pairs) (p = 0.742). Concordance for corpus atrophy in monozygotic versus dizygotic twins was 92.9% (13/14 pairs) and 86.7% (13/15 pairs), respectively (p = 0.584). Concordance for antrum intestinal metaplasia (IM) in monozygotic twins was 85.7% (12/14 pairs) and in dizygotic 73.3% (11/15 pairs) (p = 0.411). Concordance for corpus IM in monozygotic twins was 85.7% (12/14 pairs) and in dizygotic 86.7% (13/15 pairs) (p = 0.941). Among monozygotic and dizygotic subjects, the stage of gastritis was concordant in both H. pylori-positive and H. pylori-negative subjects. CONCLUSIONS: In conclusion, histological gastric mucosa alterations in monozygotic and dizygotic twins showed high rates of concordance. Furthermore, OLGA/OLGIM gastritis stages were not modulated by the zygosity of the twins.